The Effect of EPS of Biofilm on Expression of Bax and Bcl-2 Genes in Human Cervical Carcinoma Cell Line (HeLa) - Bachay, Iman A.; Alboslemy, Talib A.; Abdulla Sabeeh, Roaa; Bachii, Sheyma A. (Asian Pacific Journal of Cancer Biology, 2026)
Background: The third most common malignancy in women is cervical carcinoma (CC). worldwide and remains a major reason of cancer-related losses. between females. Even though the availability of conventional therapies, their efficacy is often limited, which has encouraged the search for novel agents that selectively target cancer cells. Recent studies suggest that bacterial biofilms may possess anticancer activity. Objective: Establish exopolysaccharides (EPS) as promising candidates for natural, cost-effective, and biologically compatible cancer therapies. Methods: In this study, the cytotoxic influence of extracellular polymeric substances (EPS) derived from Pseudomonas aeruginosa biofilms was assessed on HeLa cervical cancer cells via the methyl thiazolyl tetrazolium (MTT) test to calculate the IC50, or half-maximal inhibitory concentration. Following EPS treatment, apoptotic markers were analyzed by real-time PCR. Results: EPS exposure led to a significant, dose-dependent inhibition of HeLa cell proliferation matched to Vero cells (p<0.05). Furthermore, cervical cancer cells treated with EPS exhibited a marked rise in the expression of the pro-apoptotic gene Bax and a concomitant reduction in the expression of the anti-apoptotic gene Bcl-2 (p<0.05). Conclusion: These outcomes indicate that EPS can induce apoptosis in HeLa cells, as reflected by the upregulation of Bax and the downregulation of Bcl-2. This highlights the potential of EPS such as a promising candidate for the development of novel anticancer therapies for cervical cancer.